2024
DOI: 10.1021/acs.joc.3c02481
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Alanense A through an Intramolecular Friedel–Crafts Alkylation

Kosho Makino,
Rio Fukuda,
Shunsuke Sueki
et al.

Abstract: The first total synthesis of cadinane sesquiterpenoid alanense A, in which an intramolecular dehydrative Friedel− Crafts alkylation of 2,5-diaryl-2-pentanol is incorporated as a key step, has been achieved. The combinatorial use of p-TsOH•H 2 O as a catalyst and 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) as a solvent provides 1,1-disubstituted tetrahydronaphthalene in 97% yield. It was also found that the combination of p-TsOH and HFIP is effective for the removal of phenolic MOM ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…To demonstrate the synthetic potential of the protocol, we then evaluated the late-stage transformation of biologically active compounds (Scheme 5). First, it was found that treatment of podophyllotoxin (25) with TMSCN under the optimized Scheme 3. Substrate scope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the synthetic potential of the protocol, we then evaluated the late-stage transformation of biologically active compounds (Scheme 5). First, it was found that treatment of podophyllotoxin (25) with TMSCN under the optimized Scheme 3. Substrate scope.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Very recently, McCubbin and coworkers reported ferrocenium boronic acid 13-catalyzed dehydroxylative coupling of benzylic alcohols with carbon-and nitrogen-based borate and silane nucleophiles, in which α,α-diarylacetonitriles were obtained in moderate yields from α,α-diarylmethanols and TMSCN. [23] Recently, we have reported Brønsted acid-catalyzed intramolecular Friedel-Crafts reaction of 1,5-diaryl-1-alkynes 14 [24] as well as 2,5-diaryl-2-pentanol 16, [25] in which the use of 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) as a solvent, [26] which would effectively stabilize the cation intermediate, is critical for efficient cyclization (Scheme 2). In continuation of our studies on Brønsted acid-catalyzed transformation utilizing cationstabilizing properties of fluorous solvents such as HFIP, we herein report a direct cyanation of benzyl alcohols with TMSCN as a cyanide source.…”
Section: Introductionmentioning
confidence: 99%